Robotic-assisted resection of proximal jejunal ischemic stricture and intracorporeal robot-sewn anastomosis - Vishu Jain; Peeyush Varshney; Subhash Chandra Soni; Vaibhav Kumar Varshney; B Selvakumar (Journal of Minimally Invasive Surgery, 2022)
With the advent of robotic surgery as an effective means of minimally invasive surgery in the last decade, more and more surgeries are being performed robotically in today’s world. Robotic surgery has several advantages over conventional laparoscopic surgery, such as three-dimensional vision with depth perception, magnified view, tremor filtration, and, more importantly, degrees of freedom of the articulating instruments. While the literature is abundant on robotic cholecystectomy and highly complex hepatobiliary surgeries, there is hardly any literature on robotic small bowel resection with intracorporeal anastomosis. We present a case of a 50-year-old male patient with a symptomatic proximal jejunal ischemic stricture who underwent robotic-assisted resection and robot-sewn intracorporeal anastomosis in two layers. He did well in the postoperative period and was discharged on postoperative day 4 with uneventful recovery. We hereby discuss the advantages and disadvantages of robotic surgery in such a scenario with a review of the literature.